Avaliação de processo alternativo de biodigestão para tratamento de resíduos sólidos orgânicos domésticos - Rech, Angela Laufer (2008)
The increase in the generation of urban solid residues and the inadequate forms of treatment/disposition contribute directly with the environmental problem. In face of this situation comes the need of alternative options for the treatment of these residues, which guarantee other benefits, besides the obtained with the adequate final disposition. One of these options for the treatment of the organic fraction contained in the urban solid residues is the anaerobic digestion, which represents an attractive technology for the treatment of these residues, propitiating the transformation of the organic residue in products of aggregate value. In this context, this study aimed at to evaluate an alternative process of biodigestion for the treatment of organic domestic solid residues of the urban area. For reaching such a goal, it was firstly accomplished an environmental diagnosis aiming at the generation potential identification of the domestic residues, and at the same time it was developed a prototype for the alternative process of biodigestion. It was made the process operational parameters evaluation aiming at the optimization, through the accomplishment of a complete factorial planning, investigating the agitation effect, innocuous and water level, in the process kinetics and in the material conditions digested by the alternative process of anaerobic biodigestion, more specifically in the chemical quality of the biofertiliser, and also as complementary thing it was esteemed the application of this product generated by the corn and the soya cultivation. The results of the environmental diagnosis allowed determining a correlation for the generation potential of domestic residues estimate, as well as for the standardization of the organic fraction used in the experiment, enabling the composition reproduction of the real load in each experimental rehearsal. The proposed system for the treatment of the organic domestic solid residues was configured as an innovative method, and the experimental rehearsals accomplished in the real operation conditions, showed the influence of the analyzed parameters. Finally, the biofertiliser application estimate demonstrated the best revenues due to the application doses recommended for the corn culture and of the soya manuring.